Implementing dementia risk reduction in primary care: a preliminary conceptual model based on a scoping review of practitioners' views. (2019) - Godbee, Kali; Gunn, Jane; Lautenschlager, Nicola T; Curran, Eleanor; Palmer, Victoria J
Abstract: Primary care practitioners (PCPs) do not routinely promote dementia risk reduction. The purpose of this study was to map the published literature on the views of PCPs about dementia risk reduction, in order to identify implementation constructs and strategies crucial to the development of an implementation intervention to support dementia risk reduction in primary care. We undertook a scoping review of the PCPs' views about promoting brain health for reducing dementia risk. We searched MEDLINE, PsycINFO, CINAHL, and Embase for English-language articles published between 1995 and December 2017. We then applied the Consolidated Framework for Implementation Research (CFIR) and matched Expert Recommendations for Implementing Change to the scoping review findings in order to develop a preliminary implementation model. Eight articles reported views of PCPs about dementia prevention. Study findings were mapped to 5 of the 39 CFIR constructs: (i) knowledge and beliefs about dementia risk reduction, (ii) evidence strength and quality, (iii) relative priority, (iv) available resources, and (v) external policy and incentives. The findings suggest implementation strategies to consider in our preliminary model include (i) educational meetings, (ii) identifying and preparing champions, (iii) conducting local consensus discussions, (iv) altering incentive structures, and (v) capturing and sharing local knowledge. There have been few studies about the views of PCPs about dementia risk reduction. Implementation in the primary care setting is fundamental to early identification of risk and supporting preventive practices, but it needs to focus on more than just education for PCPs. We need more up-to-date and in-depth data on the views of PCPs about dementia risk reduction and context-specific analyses of implementation needs. Further research into effective primary care interventions to reduce dementia risk is expected to support implementation efforts.